ANALISIS IMPLEMENTASI 9 KARAKTER PADA PESERTA DIDIK SD KRISTEN GIDEON KALABAHI - Yohana Baklisama Lobang; Trisnawazti Y. Daik; Nehemia Fanpada (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Research findings based on observations and interviews with teachers and students indicate that the implementation of character education values ​​in the school has proceeded quite well, although it is not yet fully optimal. Certain traits—such as attentiveness, obedience, and honesty—are already evident in student behavior, manifested in actions like listening to teachers during lessons and adhering to school rules. However, there remain students who lack focus, talk while the teacher is explaining, and lack consistency in practicing character values ​​such as respect and sincerity.Thus, it can be concluded that while character education has been implemented, further improvement through continuous guidance is necessary to ensure that all character values ​​are fully integrated into daily school life.